Preparation and Characterization of Electroless Deposited Ni-Zn-P-TiO2(N) Composite Coating - Shao-Feng, Zhu; Chuan-Qi, Chen; Yu-Cheng, Wu (Asian Journal of Chemistry, 2013)
Nitrogen doped nano anatase TiO2 particles were prepared by nitriding treatment. The Ni-Zn-P-TiO2(N) composite coatings were prepared by adding nano TiO2(N) to electroless plating Ni-Zn-P alloy bath. The composite coatings were characterized and tested. The results show that, the maximum deposition rate occurs at 1 g dm-3 content of TiO2(N). The as-plated Ni-Zn-P-TiO2(N) composite coating consists face-centered-cubic Ni-Zn-P alloy and anatase type TiO2(N). The percentage weight of zinc, phosphorus and titanium in the composite are 6.94, 8.15 and 2.56 % respectively. The Ni-Zn-P-nano TiO2(N) composite coatings have higher hardness value, better erosion property and photodegradation effect than those of Ni-Zn-P-TiO2 composite coatings.